Long‐Term Impacts of Cropping Systems and Landscape Positions on Claypan‐Soil Grain Crop Production. (1st March 2016) - Yost, Matt A.; Kitchen, Newell R.; Sudduth, Kenneth A.; Sadler, Edward J.; Baffaut, Claire; Volkmann, Matthew R.; Drummond, Scott T.
Abstract : Sustainable grain crop production on vulnerable claypan soils requires improved knowledge of long‐term impacts of conservation cropping systems (CS). Therefore, effects of CS and landscape positions (LP) on corn ( Zea mays L.), soybean [ Glycine max (L.) Merr.], and wheat ( Triticum aestivum L.) production were evaluated from 1991 to 2010 on a claypan soil in Missouri. Replicated treatments were three CS (2‐yr mulch till corn–soybean [MTCS], 2‐yr no‐till corn–soybean [NTCS], and 3‐yr no‐till corn–soybean–wheat–cover crop [NTCSW]) and three LP (summit, backslope, and footslope). Corn yield was equivalent among CS on the summit, 13% higher for NTCS and NTCSW on the backslope, and 14% lower for NTCSW on the footslope. Soybean yield was 8% higher on the summit, 24% higher on the backslope in NTCS and NTCSW, and 12% higher on the footslope in NTCSW than MTCS. Corn yield was more stable in NTCS and NTCSW than MTCS and increased in stability from the footslope to summit. Soybean yield was less stable in NTCS and NTCSW than MTCS and LP effects on stability were similar to corn. The coefficient of variation (CV) of corn yield across years was 10% points lower in NTCS and on the footslope, and of soybean yield was 10% points lower at the footslope and summit. Wheat production was not affected by LP. Results indicate that conservation systems often can maintain grain crop productivity equal to, increase yield stability above, and reduce yield variability below those of a conventional system on claypan soils.